2004
DOI: 10.4267/2042/9435
|View full text |Cite
|
Sign up to set email alerts
|

Y a-t-il des objets plus communicationnels que d'autres ?

Abstract: Groupe de recherches interdisciplinaires sur les processus d'information et de communication (Gripic) Y A-T-IL DES OBJETS PLUS COMMUNICATIONNELS QUE D'AUTRES ?Chacun sait sur quoi portent les sciences de «l'information et de la communication». Ces deux termes suffisent d'ailleurs à faire venir à l'esprit une série de pratiques sociales, de lieux, de techniques et d'acteurs, considérés par le sens commun comme relevant de ces domaines d'activités. Un manuel parmi d'autres de la discipline indiquera donc les cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
3
0
5
Order By: Relevance
“…Les sic sont des sciences sociales qui construisent un cadre d'intelligibilité interdisciplinaire permettant de mieux comprendre la communication (Perret, 2004), en l'occurrence la communication politique. Or, cette dernière se déploie dans l'espace public, notion aujourd'hui mise à toutes les sauces théoriques (plus ou moins indigestes).…”
Section: Une Conception Dialogique De L'espace Publicunclassified
“…Les sic sont des sciences sociales qui construisent un cadre d'intelligibilité interdisciplinaire permettant de mieux comprendre la communication (Perret, 2004), en l'occurrence la communication politique. Or, cette dernière se déploie dans l'espace public, notion aujourd'hui mise à toutes les sauces théoriques (plus ou moins indigestes).…”
Section: Une Conception Dialogique De L'espace Publicunclassified
“…Ce « désir de disciplinarité » révèle, pour Jean-Baptiste Perret (2004), un trouble d'identité répandu chez les chercheurs en SIC. Effectivement on peut comprendre ce « désir » dans la mesure où pour un chercheur l'appartenance à une discipline apporte le confort douillet d'une identité qui n'est plus à forger.…”
Section: Ans Après Une Interdiscipline Sous Le Joug De Tensions Et Dunclassified
“…Jean‐Baptiste Perret () in the same special issue of Hermès observed that difficulty in distinguishing research objects is common to all “constituted disciplines.” I am assuming that by “constituted,” he means disciplines that are not from the life sciences. He goes on to say:
The desire to delineate the scope of a discipline comes up against two classic impasses related to the criteria for recognition and validity of a science: On the socio‐historical level, the circle of relativism: a discipline is what scientists in the field decide that it is.
…”
Section: Information and Communication Sciences: An Unbalanced Unionmentioning
confidence: 99%
“…Its identity relies more on a consensus within the community of scientists than on conceptual agreements, and depends above all on the state of the power relations therein. On the theoretical level, the circle of knowledge: any judgment on the relevance or validity of an assertion relies itself on the implicit recognition of a certain paradigm, hence on another judgment that cannot be proved. Hence, there is not, and there cannot be, a scientific definition of scientificity nor any “theory of a good theory.” (Perret, , p. 122) Since its official recognition and up to the present day, ICS has oscillated from one definitional axis to another. Definitions that revolve mainly around one discipline tend to be self‐serving, aimed at legitimating the place of their authors within the field.…”
Section: Information and Communication Sciences: An Unbalanced Unionmentioning
confidence: 99%
See 1 more Smart Citation